Kepatuhan Penatalaksanaan Cairan Pada Pasien yang Menjalani Terapi Hemodialisis di Rumah Sakit Swasta Yogyakarta - Yuliana Dyah Ayu Verita Kusumaningrum; Th Tatik Pujiastuti (STIKes Panti Rapih, 2020)
Background: Hemodialysis is one of the therapeutic methods for clients with end-stage renal disease. One of the problems in hemodialysis patients is the excess volume of body fluids. Fluid control is a solution to prevent complications due to excess volume of fluid.Therefore, adherence about fluid management is important to improve condition of hemodialysis patients. Objective: This study aims to describe adherence and the corelation of duration haemodialysis and IDWG with adherence of fluid management in hemodialysis patients Methods: This is quantitative descriptive method. Thirty sample was randomly. The data collection with questionnaire. Data analysis techniques are univariate using percentages and bivariat spearman corelation to describe the results of the study. Result: There is a good adherence level in the management of fluid intake 60%, enough in adherence 40%, and not good in adherence 10%. It was also known that 24 % of patients who a good adherent in fluid management had hemodialysis <4 years and 25% have an IDWG< 3 kg. There are no corelation of duration of haemodialysis p value 0,521 > 0,05 and IDWG p value 0,422 > 0,05 with adherence of fluid management in hemodialysis patients. Conclusion: It is assumed that adherence to fluid management is important for controlling IDWG in hemodialysis patients. Based on result of this study, this is important for nurses to take more intensive education to improve the adherence of hemodialysis patients in fluid management.